Ultrastructure of Terpene and Polyphenol Synthesis in the Bark of Cupressus sempervirens After Seiridium cardinale Infection - Della Rocca, Gianni; Papini, Alessio; Posarelli, Isabella; Barberini, Sara; Tani, Corrado; Danti, Roberto; Moricca, Salvatore (Frontiers in Microbiology, 2022)
Cypress Canker Disease (CCD) pandemic caused by Seiridium cardinale is the major constraint of many Cupressaceae worldwide. One of the main symptoms of the disease is the flow of resin from the cankered barks. While inducible phloem axial resin duct-like structures (PARDs) have recently been characterized from an anatomical point of view, their actual resin production is still being debated and has never been demonstrated. Although the involvement of polyphenolic parenchyma cells (PP cells) in the bark of Cupressus sempervirens after S. cardinale infection was revealed in one of our previous studya previous study by us using light microscopy, their evolution from the phloem parenchyma cells is still to be clarified. This study investigated functional and ultrastructural aspects of both PARD-like structures and PP cells by means of more in-depth light (LM), and fluorescence microscopy (FM) combined with histochemical analyses staining (using Sudan red, Fluorol Yellow, NADI Aniline blue black, and Toluidine blue staining), in addition to Transmission Electron Microscope (TEM). Two-year-old stem sections of a C. sempervirens canker-resistant clone (var. “Bolgheri”), artificially inoculated with S. cardinale, were sampled 5-7-14-21 and 45 days after inoculation, for time-course observations. FM observation using Fluorol yellow dye clearly showed the presence of lipid material in PARD-like structures lining cells of the cavity and during their secretion into the duct space/cavity. The same tissues were also positive to NADI staining, revealing the presence of terpenoids. The cytoplasm of the ducts’ lining cells was also positive to Sudan red. TEM observation highlighted the involvement of plastids and endoplasmic reticulum in the production of terpenoids and the consequent secretion of terpenoids directly through the plasma membrane, without exhibiting vesicle formation. The presence of a high number of mitochondria around the area of terpenoid production suggests that this process is active and consuming ATP. LM observations showed that PP cells originated from phloem parenchyma cells (and possibly albuminous cells) through accumulation of phenolic substances in the vacuole. Here plastids were again involved in their production. Thus, the findings of the present work suggest PARD-like structures can actually be considered PARDs or even bark traumatic resin ducts (BTRD).